The Development of Drawing Practical Skills Learning Activities with Colored Pencils Techniques Using Experiential for Prathomsuksa 3 Students - Hongsanawa, Mutita; Boontongtherng, Poosit; Rittidet, Prasobsuk (Interdisciplinary Academic and Research Journal, 2023)
Background and Aims: The most common problem in teaching art at the primary level is the lack of teachers with knowledge, ability, and expertise in art. The second problem is the lack of various teaching media and the media is not as effective as it should be. Most teachers lack knowledge and understanding of media production. Most teacher’s teaching methods still use lecture-based teaching methods, causing students to become bored and not interested in learning as much as they should, resulting in students being unable to develop their own potential. This research aimed 1) To develop drawing practical skills learning activities with colored pencils techniques using experiential for Prathomsuksa 3 students to meet the efficiency criterion of 80/80 2) To compare drawing practical skills learning activities with colored pencils techniques using experiential for Prathomsuksa 3 students, between after learning and meet the criterion of 80 3) To compare the achievement of Prathomsuksa 3 students, before and after learning with drawing practical skills learning activities with colored pencils techniques using experiential and 4) To study the students satisfaction with drawing practical skills learning activities with colored pencils techniques using experiential. Methodology: The sample group consisted of 38 Prathomsuksa 3 Students in the first semester of the academic year 2020 in Anuban Kitiya School, Maha Sarakham selected through the Cluster Sampling. The research instrument consisted of 1) learning organization plans an achievement test 3) a drawing paint practice skills assessment and 4) a satisfaction questionnaire. The statistics data were analyzed by using percentage, mean, standard deviation, and t-test Dependent Samples. Results: 1) Organizing drawing practical skills learning activities with colored pencils techniques using experiential for Prathomsuksa 3 students revealed the efficiency of 84.70/85.66 higher than the preset criterion 2) The students’ drawing paint practice skills through drawing practical skills learning activities with colored pencils techniques using experiential after learning were higher than the 80 percentage criteria, with statistical significance at the level of .05 3) The student’s achievement through drawing practical skills learning activities with colored pencils techniques using experiential after learning was higher than before learning, with statistical significance at the level of .05 and 4) Satisfied with the drawing practical skills learning activities with colored pencils techniques using experiential in high level. Conclusion: Learning activities for painting skills using the wood coloring technique that emphasizes experiences for Grade 3 students are more effective than the specified criteria. The student’s drawing and painting skills after learning are significantly higher than the criteria of 80% statistically at the .05 level, and academic achievement and satisfaction with this learning activity are still higher than the standard level.